Design of superconducting MRI surface coil by using method of moment. - Fang, J. (IEEE Transactions on applied superconductivity)
A method of moment with an enhanced model to design high-temperature superconductor (HTS) RF surface coils for magnetic resonant image (MRI) is presented. The resonant frequency and quality factor (Q) of HTS RF spiral coils are simulated using this method. The agreements of resonant frequencies and Qs between the simulation and measurement are excellent with differences less than 1 % and 3 %, respectively. The 0.2-μ m-thick YBaCuO (YBCO) thin films are deposited onto single side of 0.508-mm-thick LaAlO3 (LAO) and sapphire substrate and patterned into a spiral shape. To accurately analyze the resonant frequency and Q of a coil, an enhanced two-fluid model is employed. HTS RF coils with diameter of 65 mm for 0.2 T and 1.5 T MRI systems are designed and fabricated with the measured Q of 19 K and 23 K, respectively. In addition, the shift of resonant frequency due to the mutual coupling between two HTS spiral coils is predicted by this method, which is important for design of HTS coil arrays in an MRI system.